Du produit d’échange à l’objet symbole : de nouvelles données sur les demi-produits de type currency-bar du Val de Saône et de l’Arc jurassien - Marion Berranger; Philippe Dillmann; Philippe Fluzin; Enrique Vega; Stéphanie Leroy; Michel Aubert; Emmanuelle Delqué-Količ (Gallia)
Half-finished ferrous products, used as metal stocks to supply forge workshops, are privileged markers of the circulation of goods and the organization of exchange networks. Several thousands of these products have been inventoried, shaped like flat irons with a rolled extremity, and also known as currency bars. During this period of marked iron metallurgical development, from both a qualitative and a quantitative viewpoint, the standardized shapes of these products indicate the adoption of common standards over large geographic zones. In the scope of this article, an exceptional set of more than 70 currency-bars, found in a sector extending from Val de Saône to the surroundings of Salins-les-Bains (Jura), was studied using the latest methodologies developed in the domains of dating iron objects, the characterization of materials and sourcing analyses. This interdisciplinary approach enables us to tackle some major, still outstanding questions. The batch of half-finished products studied here constitutes the centre of a concentration extending as far as Switzerland and, in a more diffuse way, until the banks of the Seine and the southwest of Germany. Given the high number of objects available and their homogeneity, it was possible to analyse the conditions of their production, circulation and deposition. The results lead to a radical revision of previous interpretations, which were solely based on discovery contexts, and shed new light on their chrono-cultural context, which turns out to be much older than previously thought. The radiocarbon dates mainly cover the first Iron Age and extend sporadically up to the 3rd c. BC. This enables us to re-evaluate the chronology of these objects, which were previously attributed to the second Iron Age on the sole basis of discovery contexts. On the grounds of these results, we propose a new tripartite typo-chronology of half-finished products. The determination of fabrication techniques and the results of the sourcing study, based on the statistical analysis of the characteristic chemical components of the slag trapped in the half-finished products, showed that they were part of diversified and codified trade networks, involving different intermediaries. The metal derived from different production centres initially circulated in an unprocessed form, and was then transformed into standardized products in forge workshops. The multiplicity of provenances observed within the same deposit could indirectly indicate the involvement of different actors in the gathering of metallic raw materials. The study of chrono-cultural contexts, and of deposition conditions, demonstrates that these half-finished products are part of a broader trend using objects in copper and iron alloys for the payment of social obligations. These half-finished polymorphic products in iron are not only vectors of specialized trade, but also of symbolic and memorial practices.